Analisis Terkait Pembuktian Tindak Pidana Penganiayan Berdasarkan Perspektif Hukum Forensik - Adinda Kusumaning Ratri; Handar Subhandi Bakhtiar (Mahkamah : Jurnal Riset Ilmu Hukum, 2024)
The examination of a criminal case in the judicial process is essentially aimed at finding the material truth of the case. Along with the increase in criminal cases with various motives and modes, science is needed to support the interests of law enforcers. Forensic medicine or also known as judicial medicine is becoming increasingly important for the judicial process to obtain justice. This research discusses evidence in the crime of persecution from the point of view of forensic law. In this research, the author uses normative legal research methods using legal sources from primary legal materials in the form of environmental law legislation and secondary legal materials in the form of books and articles on waste management. The conclusion obtained in this paper is that Visum et Repertum is one of the valid evidence in the process of proving persecution cases, the role of forensic doctors can be as Visum et Repertum makers and doctors as expert witnesses.